Visceral Fat Cell Lipolysis and Cardiovascular Risk Factors in Obesity - Andersson, D. P.; Löfgren, P.; Thorell, A.; Arner, P.; Hoffstedt, J. (Hormone and Metabolic Research, 2011)
Visceral fat accumulation relates to cardiovascular risk factors, but the underlying mechanisms are not well understood. We investigated the role of visceral adipocyte triglyceride breakdown (lipolysis) for several risk factors of cardiovascular disease. In 73 obese women, fat mass and distribution, blood pressure, blood samples for cardiometabolic risk factors, and whole-body insulin sensitivity were determined. A subcutaneous and a visceral fat biopsy were taken. Fat cell glycerol release after stimulation with a major lipolytic hormone, noradrenaline, was measured. In simple regression analysis, visceral fat cell lipolysis, but not subcutaneous adipocyte lipolysis was related to components of the metabolic syndrome. Moreover, subjects in the highest quartile of catecholamine-induced visceral lipolysis had higher levels of systolic blood pressure, estimated liver fat, plasma levels of glucose, insulin, cholesterol, LDL-cholesterol, triglycerides and apolipoprotein B and lower whole-body insulin sensitivity than those in the lowest quartile (p=0.0004–0.048). Among subjects with the metabolic syndrome, visceral fat cell lipolysis was 40% higher than in the remaining subjects (p=0.0052). Catecholamine-activated lipolysis in visceral but not subcutaneous fat cells is associated with cardiovascular risk factors in obesity.
Keywords: adipocyte; dyslipidemia; fatty acid; glucose; insulin resistance; noradrenaline